Steinbeck in Poland - Wieslaw Ksiazek:::Creator::::::::::::
John Steinbeck with others at Wawel Castle in the courtyard. The castle was built in 1500s under auspices of Krol Zygmunt I. Steinbeck points at something with his cigar. RESTRICTED USE Original in safe